Cirurgia Obliterativa do Prolapso dos Órgãos Pélvicos - uma Opção ainda Válida? - Conde, P (2010)
Objective: To investigate the results of vaginal obliterate surgery in elderly women with pelvic organ prolapse. Design: observational retrospective study. Material and Methods: a total of 69 women with the diagnosis of pelvic prolapse were submitted to obliterative surgery in the urogynecology unit of a tertiary care hospital centre over the course of 8 years (2001 to 2008). The following data were collected from their clinical records: age, number of vaginal births, body mass index (BMI), hormone therapy, other existing diseases, type of prolapse and stage, anaesthetic risk score, duration of surgery, length of hospital stay, and short-term complications. Results: Of the 69 women studied, 31 were submitted to colpocleisis and the remaining 38 were managed by the LeFort technique. Mean age was 74.8 years with a standard deviation (sd) of 7.14 years. Average BMI was 26.2 (sd =3.76). Vaginal births were recorded in all patients. Only three patients were taking hormone therapy at the time of surgery. Sixty-three women were classified as having and anesthetic risk of II or III and 55 underwent local-regional anesthesia. Complications were reported in five cases, four of which in the first days after surgery. Nearly all were mild and resolved within the first 6 weeks. Conclusion: Complication rates appear to be low after obliterative surgery for pelvic organ prolapse in elderly women.